(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of an educational intervention in improving knowledge of motor rehabilitation among primary caregivers of stroke patients. Subjects and methods: A one-group pretest-posttest intervention study (without control) was conducted in 2025. A total of 103 primary caregivers of stroke inpatients undergoing rehabilitation were recruited. Caregiver knowledge was assessed before and after the intervention using a 20-item questionnaire covering four content domains. Results: The caregivers’ mean knowledge score increased from 9.1 ± 3.8 at baseline to 17.3 ± 2.0 post-intervention (p < 0.001). Knowledge scores across all four content domains improved significantly. Factors associated with greater knowledge gains included caregiver gender, educational level, source of information, and age. After the intervention, 88.3% of caregivers achieved a satisfactory knowledge level. Conclusion: The healthcare provider-led educational intervention significantly improved the motor rehabilitation knowledge of primary caregivers. This improvement is expected to enhance the effectiveness of post-stroke home care by addressing caregivers’ knowledge gaps.